UPAYA MENINGKATKAN HASIL BELAJAR IPS TEMA PERISTIWA DALAM KEHIDUPAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS V-B UPT. SD NEGERI 01 LIMO KAUM - Yulhendri Yulhendri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The objectives of this study are: 1) To determine the learning outcomes of students in class V-B UPT. SD Negeri 01 Limo Kaum before implementing the Jigsaw Type Cooperative Learning Model in social studies learning, the theme of events in life, the material of the Proclamation of Indonesian Independence. 2) To find out the learning outcomes of students in class V-B UPT. SD Negeri 01 Limo Kaum after the implementation of the Jigsaw Type Cooperative Learning Model in social studies learning, the theme of events in life in the material of the Proclamation of Indonesian Independence. This Classroom Action Research (CAR) consists of two cycles. The subjects in this study were students of class V-B UPT. SD Negeri 01 Limo Kaum, amounting to 34 students. This study uses a test result of social studies learning the theme of events in life in the form of multiple choices with the material of the proclamation of Indonesian independence. This test is carried out three times, namely, the pre-action test (pre test), the first learning outcome test (post test I), and the second learning outcome test (post test II). Based on the results of research on the pre-test in class V-B UPT. SD Negeri 01 Limo Kaum, the percentage of classical completeness was 58.88% (20 students). Then after being given the action, student learning outcomes in the first cycle showed the percentage of classical completeness of 73.53%. (25 students). Whereas in the second cycle the student learning outcomes were obtained with a classical completeness percentage of 91.18% (31 students). From the results of the learning test above, it can be concluded that the application of the Jigsaw Type Cooperative learning model can improve student learning outcomes in class V-B UPT. SD Negeri 01 Limo Kaum.